2009
DOI: 10.1007/s10765-009-0589-z
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flow Analyses During Throttling Processes

Abstract: This study presents an experimental investigation of the throttling process of saturated fluorocarbon refrigerants (such as R116, R218, and R610) inside capillary tubes. For the detailed two-phase flow analyses, refrigerant R218 was selected. A divided capillary tube was prepared with a set of precise pressure and temperature sensors providing detailed information about the refrigerant flow behavior inside the tube. The metastable flow regions of the superheated liquid and of the two-phase vapor-liquid mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Capillary tube CAP 2 assures continuous flow regime of SCP even when other parts of the CO2 branch or eventually of entire MPD are closed or under transient flow conditions. Pressure in the high-pressure line is measured with pressure transducer (6). Temperature and pressure of CO2 can be varied with the help of two stainless steel capillary tubes CAP 3 and CAP 4 submerged in a thermostatic bath (7) with liquid water.…”
Section: Co2 Branchmentioning
confidence: 99%
“…Capillary tube CAP 2 assures continuous flow regime of SCP even when other parts of the CO2 branch or eventually of entire MPD are closed or under transient flow conditions. Pressure in the high-pressure line is measured with pressure transducer (6). Temperature and pressure of CO2 can be varied with the help of two stainless steel capillary tubes CAP 3 and CAP 4 submerged in a thermostatic bath (7) with liquid water.…”
Section: Co2 Branchmentioning
confidence: 99%
“…The two-phase flow of vapor-liquid mixture within an adiabatic capillary tube was predicted by the numerical model similar to that employed in our previous studies [8][9][10]. More details about the design of the capillary tubes and the flow behavior of CO 2 at various inlet and outlet conditions will be provided in other article.…”
Section: Capillary Tubes On Co2 Branchmentioning
confidence: 99%
“…Another option is to replace the current capillary tubes CAP 3 and CAP 4 with another capillary tubes having the same dimensions and to verify the results measured in this study. The inner diameter can significantly vary along the capillary tube length [9,10].…”
Section: Preliminary Testsmentioning
confidence: 99%
“…Kemal et al[7] built a one-dimensional flow experiment platform for fire extinguishing agent, including HFC227ea, HFC125, water, and CO2, and finally developed a one-dimensional flow calculation module (FSP) for fire extinguishing agent by using RELAP5 software. In addition, Vacek and Vins[8] measured mass data of adiabatic throttling experiments on pure FC218 and N2 + FC218 in horizontal pipes, based on which, a twophase critical mass flow rate prediction model was established including the unstable region of superheated liquid and two-phase flow. Moreover, Vacek et al[9] carried out more in-depth adiabatic throttling experiments on the FC218 dissolved nitrogen, and found that the existence of nitrogen made the starting position of the two-phase flow significantly earlier than that of pure FC218, leading to the decrease of the mass flow rate through the capillary.…”
mentioning
confidence: 99%